Destination marketing as a team effort : the practices and experiences of three tourism entrepreneurs in northern Sweden - Axelsson, Fredric (2009)
This thesis set out to see how small and medium sized tourism entrepreneurs are using collaborative destination marketing as a complement to their use of marketing as a single destination. To accomplish this, a case study approach was used with interviews carried out with respondents from three tourism companies in the Swedish region of Norrbotten. The results show that the tourism SMEs are working within long-term partnership networks crossing muncipal and regional boarders. Perhaps as a consequence to this, the companies do not consider themselves to have any competitors, only partners. Another finding was that the reasons for entering a collaboration varies and depend on the situation for the single company. Finally the results show that while previous work have considered tourism SMEs as rather poor marketers, these companies are strong in certain aspect while weak in others. Validerat; 20101217 (root)